What are the Odds ? from Shark Attack to Lightning Strike - Kocienda, Genevieve (New York Cambridge University, 2014)
What are the odds that you will be struck by lightning ? Attacked by a shark ? Become a superstar ? This reader analyzes the chances of the incredible.
Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Glossary, Contents.
Keywords: English language; Pre-Intermediate Level